2010
DOI: 10.1155/2010/279317
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastomas with Oligodendroglial Component – Common Origin of the Different Histological Parts and Genetic Subclassification

Abstract: Abstract.Background: Glioblastomas are the most common and most malignant brain tumors in adults. A small subgroup of glioblastomas contains areas with histological features of oligodendroglial differentiation (GBMO). Our objective was to genetically characterize the oligodendroglial and the astrocytic parts of GBMOs and correlate morphologic and genetic features with clinical data.Methods: The oligodendroglial and the "classic" glioblastoma parts of 13 GBMO were analyzed separately by interphase fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…[32] A very recent report that included extensive molecular characterization of both glioblastomas and GBMOs, however, shows that GBMOs are associated with better median survival. [33] Whether molecular mechanisms that result in this histological phenotype have a synergy with the mechanisms that contribute to methylation of the promoter thereby leading to a better outcome, is perhaps a feature worth investigating in a larger set of GBMOs in future.…”
Section: Discussionmentioning
confidence: 99%
“…[32] A very recent report that included extensive molecular characterization of both glioblastomas and GBMOs, however, shows that GBMOs are associated with better median survival. [33] Whether molecular mechanisms that result in this histological phenotype have a synergy with the mechanisms that contribute to methylation of the promoter thereby leading to a better outcome, is perhaps a feature worth investigating in a larger set of GBMOs in future.…”
Section: Discussionmentioning
confidence: 99%
“…It is of clinical importance that the prognosis of GBMO is better than that of cGBM because GBMO frequently involves the loss of heterozygosity (LOH) 1p/19q, which is a good prognostic factor in oligodendroglioma, IDH1 mutation, etc. (79,20,21). Several studies report that GBMO has a significantly better prognosis than cGBM (5,9,10,22).…”
Section: Discussionmentioning
confidence: 99%
“…This subtype of GBM represents about 5-18% of all malignant gliomas. [1527] Their molecular alterations include EGFR, p53, IDH1, MGMT, loss of chromosome 1p, 9p21, 10, 19q, and gain of chromosome 7. GBM-Os may resemble GBMs on histology, but at the same time, they contain areas resembling oligodendrogliomas.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Studies have shown that patients with GBM-O tend to be younger, and the tumours are more chemosensitive, conferring a favorable prognosis. [131229] In view of the inter-tumoral differences within the same patient and, based on our current understanding of GBM, we postulate that the key to our patient's MCGBM lies in the origin of the cells responsible for malignant gliomas.…”
Section: Discussionmentioning
confidence: 99%